Surface and Curvature Tensions of Cold, Dense Quark Matter: A Term-by-Term Analysis Within the Nambu–Jona–Lasinio Model - Grunfeld, Ana Gabriela (2025)
In this paper, we conduct a thorough investigation of the surface and curvaturetensions, σ and γ, of three-flavor cold quark matter using the Nambu?Jona?Lasinio (NJL)model with vector interactions. Our approach ensures both local and global electric chargeneutrality, as well as chemical equilibrium under weak interactions. By employing themultiple reflection expansion formalism to account for finite size effects, we explore theimpact of specific input parameters, particularly the vector coupling constant ratio ηV, theradius R of quark matter droplets, as well as the charge-per-baryon ratio ξ of the finite sizeconfigurations. We focus on the role of the contributions of each term of the NJL Lagrangianto the surface and curvature tensions in the mean field approximation. We find that thetotal surface tension exhibits two different density regimes: it remains roughly constant ataround 100MeVfm−2 up to approximately 2?4 times the nuclear saturation density, andbeyond this point, it becomes a steeply increasing function of nB. The total surface andcurvature tensions are relatively insensitive to variations in R but are affected by changesin ξ and ηV. We observe that the largest contribution to σ and γ comes from the regularizeddivergent term, making these quantities significantly higher than those obtained within theMIT bag model.